Application of Maxwell damping in the dynamic analysis of masonry structures with discrete elements. (11th October 2022) - Lemos, José V.; Dawson, E.M.; Cheng, Z.
Discrete element models are widely used in the analysis of masonry structures, as they provide an effective approximation of the observed behaviour, namely for modelling collapse modes governed by the discontinuities. Assessment of the response under earthquakes is an important application of these models, which perform time domain dynamic analysis using explicit algorithms. Rayleigh damping is generally used, but its mass-proportional component has potential adverse effects, and the small steps required by explicit solutions lead to large computational costs. An alternative damping formulation employing Maxwell elements in parallel with the joint stiffness is proposed and tested. Problems involving linear elastic analysis of column bending, rocking of rigid blocks, and out-of-plane failure of masonry walls under seismic loading are examined. The proposed damping approach displayed a sound mechanical performance and is computationally efficient. These early results justify further investigation of the technique for a broader application in masonry structural dynamics.